Effect of sodium stearoyl-2-lactylate, carboxymethyl cellulose and guar–xanthan gums on muffins enriched with soybean milk powder and amaranth flour. Issue 4 (2nd October 2017) - Pérez-Carrillo, Esther; González-Fernández, Ana G.; Morales-Garza, Sylvia M.A.; Treviño-Garza, Elvira E.; Guajardo-Flores, Sara; Serna-Saldívar, Sergio O.; Sánchez-Hernández, Diana
ABSTRACT: Soybean milk powder (SMP) and amaranth flour (AF) can improve the nutritional profile of bakery products. Nonetheless, these ingredients can impart undesirable effects on batter rheology and product texture. In this study, the effect of three additives (carboxymethyl cellulose(CMC), sodium stearoyl-2-lactylate (SSL), guar–xanthan gum mix (GX)) was evaluated on batter rheology and the physical, chemical and textural parameters of muffins baked with SMP and AF. Protein content was increased in all muffins made with SMP–AF. SMP–AF also increased muffins' hardness and chewiness, but additives distinctively counteracted this effect on texture, crumb total color difference and specific volume. Of all additives, SSL ameliorated the effect of SMP–AF on the batter's rheology. Overall results indicate that muffins' nutritional value can be improved by using ingredients such as SMP and AF. Moreover, SSL can be added to muffins' formulations to compensate the effect of SMP and AF on textural and rheological characteristics.